Interferon alfa-2a in Japanese encephalitis: a randomised double-blind placebo-controlled trial. - Solomon, T; Dung, N; Wills, B; Kneen, R; Gainsborough, M; Diet, T; Thuy, T; Loan, H; Khanh, VC; Vaughn, D; White, N; Farrar, J (2003)
BACKGROUND: Japanese encephalitis virus (JEV), although confined to Asia, causes about 35000-50000 cases and 10000 deaths every year, and is the most important cause of encephalitis worldwide. There is no known antiviral treatment for any flavivirus. Results from in-vitro studies and work in animals have shown inteferon alfa has antiviral activity on Japanese encephalitis and other flaviviruses; therefore, we aimed to assess the efficacy of inteferon alfa-2a in Japanese encephalitis. METHODS: We did a randomised double-blind placebo-controlled trial of interferon alfa-2a (10 million units/m2, daily for 7 days) in 112 Vietnamese children with suspected Japanese encephalitis, 87 of whom had serologically confirmed infections. Our primary endpoints were hospital death or severe sequelae at discharge. Analysis was by intention to treat. FINDINGS: Overall, 21 children (19%) died, and 17 (15%) had severe sequelae. Outcome at discharge and 3 months did not differ between the two treatment groups; 20 children in the interferon group had a poor outcome (death or severe sequelae), compared with 18 in the placebo group (p=0.85, difference 0.1%, 95% CI -17.5 to 17.6%), there were no long-term side effects of interferon. INTERPRETATION: The doses of interferon alfa-2a given in this regimen did not improve the outcome of patients with Japanese encephalitis.